PpSnRK1α overexpression alters the response to light and affects photosynthesis and carbon metabolism in tomato. Issue 4 (22nd August 2021) - Liang, Jiahui; Zhang, Shuhui; Yu, Wenying; Wu, Xuelian; Wang, Wenru; Peng, Futian; Xiao, Yuansong
Abstract: Sucrose nonfermentation 1 (SNF1) related kinase 1 (SnRK1) is a central energy sensor kinase in plants and a key switch regulating carbon and nitrogen metabolism. Fruit quality depends on leaf photosynthetic efficiency and carbohydrate accumulation, but the role of peach ( Prunus persica ) SnRK1 α subunit ( PpSnRK1α ) in regulating leaf carbon metabolism and the light signal response remains unclear. We studied the carbon metabolism of tomato leaves overexpressing PpSnRK1α and the responses of PpSnRK1α ‐overexpressing tomato leaves to light signals. Transcriptome, metabolome, and real‐time quantitative polymerase chain reaction analyses revealed that uridine 5′‐diphosphoglucose, glutamate, and glucose‐6‐phosphate accumulated in tomato leaves overexpressing PpSnRK1α . The expression of genes (e.g., GDH2, SuSy ) encoding enzymes related to carbon metabolism (e.g., glutamate dehydrogenase (GDH2; EC: 1.4.1.3), sucrose synthase (SS; EC: 2.4.1.13)) and chlorophyllase ( CLH ) encoding chlorophyllase (EC: 3.1.1.14), which regulates photosynthetic pigments and photosynthesis, was significantly increased in PpSnRK1α ‐overexpressing plants. PpSnRK1α overexpression inhibited the growth of hypocotyls and primary roots in response to light. The chlorophyll content of the leaves was increased, the activity of SS and ADPG pyrophosphatase (AGPase; EC: 2.7.7.27) was increased, and photosynthesis was promoted in PpSnRK1α ‐overexpressing plants relative to wild‐type plants. Under light stress, the net photosynthetic rate of plants was significantly higher in plants overexpressing PpSnRK1α than in wild‐type plants. This indicates that PpSnRK1α promotes the accumulation of carbohydrates by regulating genes related to carbon metabolism, regulating genes related to chlorophyll synthesis, and then responding to light signals to increase the net photosynthetic rate of leaves.